Cyclone Ockhi Induced Upwelling and Associated Changes in Biological Productivity in Arabian Sea. Issue 1 (2nd January 2021) - Ganguly, Debojyoti; Suryanarayana, K.; Raman, Mini
Abstract: In this study, the effect of severe tropical cyclone Ockhi on the physical and biological changes in ocean properties has been investigated. Winds from SCATSAT-1 was used for estimating the cyclone induced Ekman pumping. The role of ocean stratification, cyclonic wind stress, eddies and cyclone translation speed on the post cyclone oceanic response has been investigated. 8-day composite data of winds, sea surface temperature (SST), chlorophyll and sea level anomaly (SLA) have been analyzed for pre-cyclone, during cyclone and after cyclone period to understand the effect of wind forcing on the ocean variables. It was observed that there was a significant phytoplankton bloom like concentration along with 2-3 °C drop in SST after the passage of Ockhi. Thermocline displacements of up to 56 m were observed along the cyclone track. SLA data analyzed for the period shows formation of a cyclonic cold core eddy and weakening of anticyclonic warm core eddies. The entire cyclone track was divided into 12 track points based on the 12 hourly position and the change in SST and chlorophyll analyzed. The maximum change in chlorophyll and SST was observed where the cyclone was slowest and mixed layer shallow.